2017
DOI: 10.17586/2220-8054-2017-8-4-471-475
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microtube formation with walls, containing Fe3O4 nanoparticles, via gassolution interface technique by hydrolysis of the FeCl2 and FeCl3 mixed solution with gaseous ammonia

Abstract: In this work, microtubes with walls, containing Fe 3 O 4 nanoparticles, obtained by "rolling up" of the interfacial films, were synthesized by the gas-solution interface technique (GSIT), using a mixture of aqueous solutions of FeCl 2 and FeCl 3 and gaseous ammonia. The synthesized microtubes were characterized by Scanning Electronic Microscopy (SEM), Energy-Dispersive X-ray spectroscopy (EDX), X-Ray Diffraction analysis (XRD) and magnetization measurements. It was established that under optimal synthetic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In this work we employed ascorbic acid to avoid oxidation of the Fe II solution. Earlier it was demonstrated that the Fe 3 O 4 film and microtubes are formed on the surface of the FeCl 2 /FeCl 3 solution without ascorbic acid addition . Ascorbic acid was added to the FeCl 2 solution in a concentration equal to 0.025 m .…”
Section: Methodsmentioning
confidence: 99%
“…In this work we employed ascorbic acid to avoid oxidation of the Fe II solution. Earlier it was demonstrated that the Fe 3 O 4 film and microtubes are formed on the surface of the FeCl 2 /FeCl 3 solution without ascorbic acid addition . Ascorbic acid was added to the FeCl 2 solution in a concentration equal to 0.025 m .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, nanomembrane fabricated via chemical synthesis could also be rolled by utilizing surface tension at the air–solution interface . For example, treating the NaAsS 2 solution with a mixture gas flow of HCl and air, and As 2 S 3 microtubes with diameters ranging from 20 to 100 µm would form after drying.…”
Section: Rolling Mechanismmentioning
confidence: 99%
“…For example, treating the NaAsS 2 solution with a mixture gas flow of HCl and air, and As 2 S 3 microtubes with diameters ranging from 20 to 100 µm would form after drying. The mechanism behind the rolling‐up process could be explained as following: as the reaction product—As 2 S 3 nanomembrane—is hydrophobic and does not sink in the solution, the nanomembrane would exist at the interface of air and solution. During the drying process, the surface tension at the air–layer interface exhibits a larger value than at the side of layer–solution interface.…”
Section: Rolling Mechanismmentioning
confidence: 99%
“…For example, novel metamaterials were obtained using this approach [1] and new types of 3D devices with small form factors [2][3][4]. There are also known works devoted to the synthesis and research of nanoscrolls of hydrosilicates of metals [5][6][7][8], as well as microtube of a number of oxides [9,10], fluorides [11] and sulfides of metals [12]. As shown by the authors of these works, the reason for this rolling up is mechanical forces that arise inside planar structures due to density or composition gradients.…”
Section: Introductionmentioning
confidence: 99%